(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
Effects of viscous dissipation and radiation on MHD natural convection in oblique porous cavity with constant heat flux is studied numerically in the present article. The right inclined wall is maintained at a constant cold temperature T_c and the left inclined wall has a constant heat flux q with length S, while the remainder of the left wall is adiabatic. The horizontal walls are assumed to be adiabatic. The governing equations are obtained by applying the Darcy model and Boussinesq approximations. COMSOL's finite element method is used to solve the non-dimensional governing equations together with specified boundary conditions. The governing parameters of this study are Rayleigh number (Ra=10,100,200,250,500 and 1000), Hartmann number (0 ≤ Ha ≤ 20), inclination angle of the magnetic field (0^◦≤ ω ≤ π/2), Radiation (0≤ R ≤15), the heater flux length (0.1≤ H ≤1) and inclination angle of the sloping wall (−π/3 ≤ φ ≤ π/3). The results are considered for various values of the governing parameters in terms of streamlines, isotherms and average Nusselt number. It is found that the intensity of the streamlines and the isotherm patterns decrease with an increment in Hartmann number. The overall heat transfer is significantly increased with the increment of the viscous dissipation and the radiation parameters.